Characterization of a partial-body irradiation model with oral cavity shielding in nonhuman primates. (2nd January 2020) - Accardi, Michael V.; Donini, Oreola; Rumage, Adam; Ascah, Alexis; Haruna, Julius; Pouliot, Mylène; Bujold, Kim; Huang, Hai; Wierzbicki, Wieslaw; Stamatopoulos, John; Naraghi, Houman; Measey, Thomas; et al.
Abstract: Purpose: Characterization of a novel partial-body irradiation (PBI) shielding strategy in nonhuman primates (NHP; rhesus macaques), aimed at protecting the oral cavity, with respect to various gastrointestinal acute radiation syndrome (GI-ARS) syndrome parameters as well as buccal ulceration development. Materials and methods: NHPs were irradiated using a Cobalt-60 gamma source, in a single uniform dose, ranging from 9–13 Gy and delivered at 0.60–0.80 Gy min −1 . Animals were either partially shielded via oral cavity shielding (PBIOS ) or underwent total-body irradiation (TBI). Results: Clinical manifestations of GI-ARS, and also radiation-induced hematology and clinical chemistry changes, following PBIOS were comparable to the PBI NHP GI-ARS model utilizing shielding of the distal pelvic limbs and were significantly milder than TBI at similar radiation doses. Nadir citrulline levels were comparable between PBIOS and TBI but signs of recovery appeared earlier in PBIOS -treated animals. The PBIOS model prevented oral mucositis, whereas the TBI model presented buccal ulcerations at all tested radiation dose levels. Conclusions: Taken together, these results suggest that the PBIOS model is a suitable alternative to traditional PBI. For GI-ARS investigations requiring orally administered medical countermeasures, PBIOS confers added value due to the prevention of oral mucositis over traditional PBI.